Anti-Bullying Awareness Program for Students at Mambaul Falah Pakal Kindergarten - Rifai, Muhammad Rifai; Dewani, Hardhika Wahyu (Journal Ligundi of Community Service, 2025)
Bullying is a common issue within the school system. Consequently, Mambaul Falah Pakal Kindergarten, located on Jl. Beji Rahayu Kav No. A1-A2 Surabaya, strives to address and prevent bullying by offering various student mentoring programs. Drawing on research and literature from 2020–2025, this article discusses the importance of student mentoring as a strategy to prevent bullying in the school environment. Bullying in Kindergarten: Bullying is an act of violence where an individual who is physically, verbally, or psychologically weaker is harmed through the use of force or threats. This phenomenon frequently occurs among school-aged students, including kindergarteners. Student mentoring at Mambaul Falah Kindergarten Surabaya aims to prevent bullying by conducting anti-bullying awareness sessions and providing an overview of the impact caused by bullying.